The role of HOX genes in head and neck squamous cell carcinoma - Platais, Christopher; Hakami, Fahad; Darda, Lav; Lambert, Daniel W.; Morgan, Richard; Hunter, Keith D. (Journal of oral pathology & medicine, 2016)
Recent decades have witnessed the publication of numerous studies reporting alterations in the genome and transcriptome of head and neck squamous cell carcinoma (HNSCC). Currently, the utilisation of these alterations as biomarkers and targets for therapy is limited and new, useful molecular characteristics are being sought. Many of the published HNSCC gene expression profiles demonstrate alterations in the expression of HOX genes. These are a family of Homeobox‐containing genes which are involved in developmental patterning and morphogenesis in the embryo, and which are often aberrantly expressed in cancer. The 39 HOX genes found in the human genome are arranged in four paralogous groups at different chromosomal loci. These control a wide range of cellular processes, including proliferation and migration, which are relevant in the context of cancer development. In this review article, we will outline the biology of HOX genes in relation to cancer and summarise the accumulating evidence for their role in the development of HNSCC and the possibility that they could be a therapeutic target in this malignancy. We will also identify areas where our current understanding is weak to focus future work and appraise the ongoing strategies for pharmacological intervention.